Impact of Climate Change on Agriculture in Kavre District, Nepal - Giri, Mira; Dahal, Dhundi Raj (Journal of APF Command and Staff College, 2021)
This study aims to assist the impact of climate change on agriculture in Banepa municipality, as a case study to the local climatic trends and its impacts, vulnerability, and adaptation. The study was conducted among the household of ward no. one to eleven except two and six in the municipality. A questionnaire survey, field observation, in-depth interview, and focus group discussion, methods were adopted for the information collection, cross-validation with verification, and using the secondary source of the information. Monthly precipitation and monthly minimum and maximum air temperatures data of Dhulikhel station were used to study their annual and seasonal trends.Agriculture is one of the vulnerable sectors of the impact of climate change. Trend analysis of temperature and precipitation over 27 years indicates that this region is facing various weather variability. The annual mean of the minimum temperature was showing the highest (13.530C) in 2014 and the lowest (7.860C) in 2001. The trend analysis shows that the annual average minimum temperature has also been increasing per year. Drought, delay in monsoon, hailstorm,and heavy rainfall are major challenges in agriculture.The study concluded that climate change affected the negative impact on agriculture in the Banepa Municipality of Kavre. The existing local and institutional strategies are not sufficient and sustainable to cope with climatic vagaries. There is a proactive need for climate change adaptation measures to address the negative impact of climate change in agriculture to sustain the food and nutrition security in the community through institutional support and long-term agricultural policy and strategic plan.